Innovative teachers: structure and development in the field of physical education - Morozova L.V.; Melnikova T.I.; Vinogradova O.P.; Butakova E.D. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to formation of competencies for creative innovative activities of future physical education teachers. Methods and structure of the study. The research was conducted using a competence-based approach to enhancing the creative abilities of physical education instructors. The methodology was grounded in the principles of system-based, factorial, and comparative analysis. Results and conclusions. The essential elements of a creative individual are identified: innovative thinking, a focus on excellence, self-improvement, and adaptability. The constituent elements of the creative mindset of future physical education instructors are unveiled: a value-driven approach, a procedural framework, a reflective mindset, and a personal touch. It has been determined that the creative potential of a future professional is rooted in the cultivation of creative abilities and the pursuit of personal growth.